Kesadaran, Pengetahuan Perpajakan dan Penghasilan Wajib Pajak Terhadap Tingkat Kepatuhan Wajib Pajak dalam Membayar Pajak Bumi dan Bangunan - Linda Sulistiyowati; Dyah Ratnawati (Journal of Management and Bussines (JOMB), 2023)
This research aims to examine the influence of Taxpayer Awareness, Tax Knowledge, and Taxpayer Income on the Level of Taxpayer Compliance in Paying Land and Building Taxes carried out in Sumberwuluh Village, Dawarblandong District, Mojokerto Regency. The research method is quantitative with the data analysis used is multiple linear regression analysis using SPSS version 22 software. Research Results a) t test on the taxpayer awareness variable (X1), obtained a significance value of 0.376 > 0.05, so it can be concluded that H0 accepted and Ha rejected; b) T test on the tax knowledge variable (X2), obtained a significance value of 0.014 < 0.05, so it can be concluded that H0 is rejected and Ha is accepted; c) t test on taxpayer income (X3), obtained a significance value of 0.00 < 0.05. In conclusion, taxpayer awareness does not influence the level of taxpayer compliance, while tax knowledge and taxpayer income influence the level of taxpayer compliance in paying land and building taxes. Keywords: Taxpayer Awareness, Tax Knowledge, Taxpayer